LB-002 Unravelling The Relationship Between Mucins And Mucolytic Bacteria During Intestinal Inflammation. (9th June 2014) - Thursby, E; Kavanaugh, D; Crost, EH; Tailford, LE; Gunning, P; Tremelling, M; Watson, A; Juge, N
Abstract : Introduction: The epithelium in the human GI tract is coated in protective mucus, which acts as a key component of the intestinal barrier. In the colon, mucus consists of an inner, impenetrable and firmly attached layer, and an outer layer that provides a habitat for commensals. Mucins that make up mucus are decorated in a diverse array of O-glycans, providing both nutrients and attachment sites for microbes. Dysbiosis of the microbiota and alterations in mucin glycosylation are often associated with Inflammatory Bowel Disease (IBD). Whether these factors are causes or consequences of inflammation remains to be elucidated. Methods: We are using a multidisciplinary approach to uncover the molecular mechanisms leading to loss of barrier function in IBD. These include the isolation and purification of mucins and bacteria from mucosal lavages of patients undergoing colonoscopy. Mucin glycosylation is analysed by lectin screening using immunohistochemistry, AgPAGE gradient gel electrophoresis, and atomic force microscopy (AFM). This will be complemented by detailed structural analysis by mass spectrometry and High Performance Anion Exchange Chromatography (HPAEC). The composition of specific mucin-degrading groups is analysed by qPCR, and will be complemented by 16S metagenomic sequencing of the total mucosa-associated bacterial population. Results: Mucins were purified from mucosal lavage and visualised with AFM, revealing the presence of fibrous chains with contour lengths ranging from tens of nanometers to several microns. The binding specificity of various lectins was utilised in force spectroscopy measurements to assess the affinity of their cognate sugars at the molecular scale. Preliminary data indicates that this technique is a promising new approach which can be further utilised to explore the spatial distribution of glycans in human intestinal mucins and investigate differences in varying disease states. In parallel, bacterial DNA was extracted from mucosal lavages, and quantitative PCR carried out to analyse the composition of the mucosa-associated bacterial population. Preliminary qPCR analysis revealed a trend towards an altered microbial profile in patients with inflammation. Conclusion: Dysbiosis of the microbiota and alterations in mucosal barrier are often associated with IBD. Deciphering whether these factors are causes or consequences of inflammation will impact on the choice of therapeutic intervention strategies. Assessing the changes in mucin-degrading bacteria and mucin glycosylation at the human mucosal surface will provide evidence-based strategies to select and/or design effective treatments to restore barrier function. Disclosure of Interest: None Declared.